Surgeon's experience and clinical outcome after retropubic tension‐free vaginal tape—A case series. (13th March 2020) - Holdø, Bjørn; Møllersen, Kajsa; Verelst, Margareta; Milsom, Ian; Svenningsen, Rune; Skjeldestad, Finn Egil
Abstract: Introduction: The retropubic tension‐free vaginal tape procedure has been the preferred method for primary surgical treatment of stress and stress‐dominant mixed urinary incontinence in women for more than 20 years. In this study, we assessed associations between surgeon's experience with the primary tension‐free vaginal tape procedure and both perioperative complications and recurrence rates. Material and methods: Using a consecutive case‐series design, we assessed 596 patients treated with primary retropubic tension‐free vaginal tape surgery performed by 18 surgeons from 1998 through 2012, with follow up through 2015 (maximum follow‐up time: 10 years per patient). Data on perioperative complications and recurrence of stress urinary incontinence from medical records was transferred to a case report form. Surgeon's experience with the tension‐free vaginal tape procedure was defined as number of such procedures performed as lead surgeon (1‐19 ["beginners"], 20‐49 and ≥50 procedures). All analyses were done with a 5% level of statistical significance. We applied the Chi‐square test in the assessment of perioperative complications. The regression analyses of recurrence rate by number of tension‐free vaginal tape procedures performed were restricted to the three surgeons who performed ≥50 procedures. Results: We found a significantly higher rate of bladder perforations ( P  = .03) and a higher rate of urinary retentions among patients whose tension‐free vaginal tape procedures were performed by "beginners" ( P  = .06). We observed a significant reduction in recurrence rates with increasing number of tension‐free vaginal tape procedures for one surgeon ( P  = .03). Conclusions: Surgeon's experience with the tension‐free vaginal tape procedure is associated with the risk of bladder perforation and urinary retention, and may be associated with the long‐term effectiveness of the procedure.